Penilaian Kinerja PT Bank X dalam Mengelola Asset dan Kewajiban Berdasarkan Analisis Resiko dan Analisis Return - Yusuf, Muhammad (Binus Business Review, 2010)
Performance financial evaluation became a primary indicator for management, especially a bank. This research evaluated asset and liability management of PT Bank X to describe its risk and return, by using financial ratios. The results found that performance ratios of PT Bank X decreasingly, where interest margin and net margin decreased to negative. This because of interest expenses and other operational expenses increased. Risk evaluation based on liquidity ratio were also decreasing in 2006 â 2007, because of the most assets of the bank became illiquid assest and default credits. On the other hand, this conditions became worse because of âRushâ, many of their customers took their money out from the bank on the same period. In 2008, bank has reduced their default credits succesively and made its liquiditiy better than previous year. Bad quality of credit management and control made the bank budgets their bad allowances for default credits higher and made bankâs capital risk higher too. Finally, all of bankâs capital was financed with their liabilities. The other hand, bankâs operating risk were recovered slowly, by organzation rationalization to reduce number of employees, as efficiency also. But this effort, indeed, made employee expenses increasing because management must pay golden-shake hand costs to employees.Â